IMPLEMENTATION OF INTERFAITH HARMONY VALUES IN KEDUNG ASRI VILLAGE, TEGALDLIMO DISTRICT, BANYUWANGI REGENCY - M Islah Fuadi; Moch Imam Machfudi; Saihan Saihan (International Journal of Teaching and Learning, 2025)
Religious conflicts in Indonesia often arise from various factors, including competition for political power, resources, and differences in doctrinal beliefs. In heterogeneous societies, a lack of understanding and respect for religious diversity potentially triggers social tensions and disintegration. Islamic religious education plays a strategic role in promoting tolerance by fostering knowledgeable, intelligent, and dignified students, as well as teaching appreciation for diversity. This study aims to analyze the implementation of interfaith harmony values in the village of Kedung Asri, Tegaldlimo district, Banyuwangi regency. A quantitative research method was employed involving the distribution of questionnaires to residents from diverse religious backgrounds, with purposive sampling used to assess attitudes and practices of harmony. Collected data were analyzed using descriptive statistics to identify levels of dialogue, tolerance, and harmonious behavior within the community. The questionnaire was designed based on measurable indicators relevant to the values of harmony. Results indicate that the community of Kedung Asri actively engages in interfaith dialogue that fosters mutual understanding and respect for differences. A high level of tolerance is reflected in the participation of residents in various social and religious activities without discrimination. The implementation of harmony values is clearly expressed through social cooperation, respect among religious communities, and the central role of religious leaders in facilitating harmony. The discussion highlights the importance of inclusive communication strategies and the strengthening of character education as the main foundation for maintaining harmony. The study concludes that the implementation of interfaith harmony values in Kedung Asri is effective with strong support from the community and local leaders. However, gaps remain concerning differences in religious perceptions and the need for more systematic dialog strategies to address modern challenges. This research provides important recommendations for the development of policies and social programs aimed at strengthening harmony in multicultural Indonesian society.